Response Of Okra (Abelmoschus esculentus L.) To The Integrated Application Of NPK, Desert Lion Foliar And Urea Fertilizers - Habbibah Aggrey; Michael Kwabena Osei; Joseph Sarkodie-Addo; Kwame Yaw-kan Kojo; Richard Mensah Dormatey; Eric Danquah; Mary Otiwaa Osei Asante; Philip Ghanney; Agbesi Keteku (AGRICA, 2023)
A field trial was conducted to investigate the effect of NPK 15:15:15 at 50:30:30 kg ha-1, Desert-Lion foliar fertilizer (DL) at 25 ml/15 l water, Urea at 50 kg ha- 1, P2O5 and K2O at 30 kg ha-1+Desert-lion foliar fertilizer at 25 ml/15 l water (DPK) and P2O5 and K2O at 30 kg ha-1+ urea at 50 kg ha-1 + Desert-lion foliar fertilizer at 25 ml/15 l water (DPKU) on the performance of okra. A randomized complete block design was used with four replications. Data were collected on growth and yield components. The DPKU, DPK, sole urea and NPK exhibited superior performances in plant height, leaf and branch per plant compare with the sole DL and the control. The DPKU, DPK, NPK and sole urea recorded 40, 39, 38 and 37 fruits per plant respectively, compared to 23 and 35 registered by sole DL and the control respectively. The NPK, DPKU, DPK and sole urea recorded significant total fruit yields of about 7.5 t ha-1, 7.5 t ha-1, 6.5 t ha-1 and 6 t ha-1 respectively, whiles sole DL and the control produced 2.5 t ha-1 and 1.5 t ha-1 yields respectively. The treatment combinations, sole Urea and NPK performed higher than the sole DL. Therefore, for high yield of okra, the DL at 25 ml/15 liters of water should be applied with basal application of 30 kg ha-1 of P2O5 and K2O + urea at 50 kg ha-1 at flowering.